Women's Images in Iksaka Banu's Novel Rasina: A Feminist Literary Criticism Study: Citra Perempuan dalam Novel Rasina Karya Iksaka Banu: Kajian Kritik Sastra Feminis - Miner Sintia; Irianto Ibrahim; Sumiman Udu; Andi Muh. Ruum Sya’baan (CASA CENDEKIA MEDIA, 2026)
This study is motivated by the need for a critical reading of women's representations in colonial-themed literary works, since women's bodies, voices, and social positions are often shaped by patriarchal power relations as well as layered colonial systems. This study aims to describe the image of women in the novel Rasina by Iksaka Banu, covering self-image (physical and psychological aspects) and social image (family and colonial society). A qualitative approach with a descriptive-interpretative design was employed through reading and note-taking techniques, with textual units from the novel Rasina (2023) as the main data source. Data were analyzed through identification, classification, interpretation, and conclusion drawing within Ruthven's feminist literary criticism framework. The findings reveal that Rasina is portrayed as possessing physical allure alongside a wounded, violated body, experiencing psychological trauma and fear, and occupying a subordinate position both domestically and as an enslaved indigenous woman within the colonial legal system. These findings affirm that Rasina represents the layered oppression of indigenous women arising from the intersection of gender, class, and race within colonial structures.